A comparative analysis of cloud computing services using multicriteria decision analysis methodologies. (19th March 2015) - Papathanasiou, Jason; Kostoglou, Vassilis; Petkos, Dimitris
Cloud computing is changing rapidly the way users perceive the use of computer functions and resources as well as it enables the development of more complex business models. New issues emerged by this ongoing trend, especially by privacy advocates as regards to the way cloud services providers control totally the communication and data exchanged between them and the users. It is however generally considered a reliable way to add features to the existing technical capabilities and to increase business capacity on the fly without at the same time making costly new investments in IT infrastructures. This paper focuses on the users' perspectives towards the most popular free services providers; goal programming techniques assessed the weighs of the selected criteria in order to implement multi-criteria methodologies. The results provided an opportunity to gain insights on the users' demands and expectations and to evaluate the level of trust towards these new services.